Some correlates of basic mathematical understanding of elementary mathematics teachers in the Division of Quezon City - Mamauag, Rosemarie Lumido 1946- (1976)
This study was designed to determine some factors that affect the teachers' basic mathematical understanding. A measure of a teacher's understanding of basic mathematical concepts was obtained through the administration of an objectively scored multiple-choice test chosen from "A Teacher's Test on Basic Mathematical Understanding" which was developed by Dr. Abracia. The findings of the study showed that the length of service, mathematics units earned, in-service education and age were significantly related to the basic mathematical understanding of teachers. The type of institution and mathematical understanding have no relationship, hence, it cannot serve as a basis for assigning teachers to mathematics classes.
Vita.
Thesis (M.Ed.)--University of the Philippines, Diliman.
Keywords: Mathematics teachers -- In-service training -- Philippines -- Quezon City; Elementary school teachers -- Philippines -- Quezon City; Effective teaching -- Philippines -- Quezon City; Mathematics -- Study and teaching (Elementary) -- Philippines -- Quezon City